Estudo teórico da interação entre nanotubos de carbono, nitreto de boro e nitreto de gálio com compostos cisplatina e cisplatina-metila usados no tratamento de câncer - PEREIRA, Jurandir Santos (2021)
This work presents a theoretical study on carbon nanotubes, boron nitride and Thrush nitride interacting with cisplatin compounds and a cisplatin-methyl non branched chain derivative, through simulations of first principles, based on the theory of density functional (FTD). Simulation calculations were performed in the SIESTA computer program. The structural, energetic and electronic properties of the cisplatin and cisplatin-methyl molecule, adsorbed internally and externally in carbon nanotubes (CNT) composed of 96 atoms, Boron nitride (BN) and Galium nitride (GaN) both composed of equal amounts of atoms, were analyzed. All possible stable conformers of the drugs were investigated by means of geometry optimizations at the theory level, using as a DZP base for platinum. The results show that the electronic properties of the nanotubes are affected by adsorption of the cisplatin and cisplatin methyl molecules. After internal and external adsorption of cisplatin and cisplatin methyl internal adsorption, it was observed that the energy gap decreased in all nanotubes due to the levels introduction of of defects in the gap region. In the pure CNT the gap was 1.34 eV, when it interacts with cisplatin began to have a gap of 1.28 eV (internal and external) and with cisplatin-methyl the gap went to 1.26 eV. In pure GaN the gap, which was 2.47 eV, when adsorbed to cisplatin, internally passes to 2.14 eV and externally passes to 1.60 eV with cisplatin-methyl passes to 2.26 eV. In pure BN, the gap, which was 4.53 eV, with cisplatin inclusion and then cisplatin methyl, both passed to 2.87 eV and when adsorbed externally with cisplatin passes to 2.73 eV. In addition, quantum calculations of internal and external adsorption verified that all single-walled CNT, BN and GaN nanotubes adsorbed the cisplatin and cisplatin-methyl molecules spontaneously through the chemisorption process.